Antimicrobial susceptibility and clinical findings of significant anaerobic bacteria in southern Spain. (October 2019) - Cobo, Fernando; Rodríguez-Granger, Javier; Pérez-Zapata, Inés; Sampedro, Antonio; Aliaga, Luis; Navarro-Marí, José María
Abstract: The objectives of this study were to report on the antimicrobial susceptibility of 276 clinically significant anaerobic bacteria belonging to the major genera isolated between May 2017 and November 2018 in a tertiary hospital in Granada (Spain) and to describe key clinical features of the patients. Species identification was performed by MALDI-TOF MS. Antimicrobial susceptibility tests were performed against penicillin, amoxicillin-clavulanic, imipenem, meropenem, moxifloxacin, clindamycin, metronidazole, vancomycin, and piperacillin-tazobactam using the gradient diffusion technique and EUCAST breakpoints (except for moxifloxacin). The most frequent anaerobes were Bacteroides (29.7%; n = 82), Clostridioides difficile (15.9%, n = 44), Prevotella (10.8%, n = 30), and Propionibacterium (10.7%, n = 25). Metronidazole was not universally active against all genera tested, and some isolates showed resistance to this drug. Almost all tested anaerobes were susceptible to carbapenems and amoxicillin-clavulanate except for Clostridioides difficile (resistance rate of 94%) and Bacteroides (19%), respectively. High overall resistance rates to clindamycin were observed, especially for genera Finegoldia (54%), Bacteroides (49%), and Prevotella (40%). Resistance rates to carbapenems and amoxicillin-clavulanate were very low for the majority of tested genera but were high for Clostridioides difficile and Bacteroides spp., respectively. Resistance to clindamycin was very high, especially for Bacteroides, Finegoldia magna, Prevotella and Peptoniphilus . Routine antimicrobial susceptibility testing for anaerobes contributes information on the global situation and allows empirical therapies to be selected in accordance with local data on resistant strains. Highlights: Metronidazole was not universally active against all anaerobes. Resistance rates to carbapenems and amoxicillin-clavulanate were very low. Resistance rates of almost all genera to clindamycin were very high. Routine antimicrobial susceptibility testing is highly recommended.